Association of cardiorespiratory hospital admissions with ambient volatile organic compounds: Evidence from a time-series study in Taipei, Taiwan. (August 2021) - Qiu, Hong; Bai, Chyi-Huey; Chuang, Kai-Jen; Fan, Yen-Chun; Chang, Ta-Pang; Yim, Steve Hung-Lam; Ho, Kin-Fai
Abstract: As important precursors of ozone and secondary organic aerosols, the harmful impact of exposure to ambient volatile organic compounds (VOCs) is of public health interest. However, few studies have investigated the health risks of numerous individual VOC species. This study linked the daily concentrations of 54 C2–C11 VOC species monitored from the Wanhua Photochemical Assessment Monitoring Station and hospital admissions for cardiorespiratory diseases in Taipei, Taiwan, from the National Health Insurance Research Database. A standard time-series approach entailing a series of sensitivity analyses was applied to investigate the short-term health risks of exposure to VOC subgroups and species. Consistent associations of all VOC subgroups and main species with chronic obstructive pulmonary disease (COPD) hospitalizations were demonstrated. In addition, associations of the C5–C6 alkanes, C2–C3 alkenes, toluene, and xylene with asthma hospitalizations were found, as were associations of aromatic hydrocarbons with hospitalizations for heart failure. An interquartile range increase in total VOC exposure at lag0 day (102.6 parts per billion carbon) was associated with increments of 1.84% (95% confidence interval: 0.54%–3.15%), 1.65% (0.71%–2.60%), and 1.21% (0.36%–2.07%) in hospitalizations for asthma, COPD, and heart failure, respectively. The effect estimates were robust with data excluding extreme values, the second pollutant adjustment for PM2.5 and O3, and the Bonferroni correction. The associations of ambient VOC exposure with cardiorespiratory hospitalizations in Taipei serve as a reference for VOC regulations and ozone control strategies. Graphical abstract: Image 1 Highlights: The cardiorespiratory risk of ambient VOCs were observed in Taipei. All VOC subgroups and main species were associated with COPD hospitalizations. Some alkanes, alkenes, and aromatics were associated with asthma hospitalizations. Aromatic VOCs were associated with hospitalizations for heart failure.